Absorption kinetics of low‐dose chewable aspirin – implications for acute coronary syndromes. (January 2015) - Hobl, Eva‐Luise; Schmid, Rainer W.; Stimpfl, Thomas; Ebner, Josef; Jilma, Bernd
Abstract Background This study describes the implications of the pharmacokinetics of low‐dose chewable aspirin for acute coronary syndromes. Current guidelines recommend the administration of 162–325 mg aspirin chewing tablets for the treatment of acute myocardial infarction. Although aspirin is widely used and a cornerstone in myocardial infarction, there is no information available on the pharmacokinetics of low doses of chewable aspirin. Materials and methods This prospective trial assessed the pharmacokinetics of acetylsalicylic acid and its metabolite salicylic acid after intake of 162 mg chewable low‐dose aspirin in 35 healthy volunteers. Plasma drug and metabolite levels were analysed using high‐performance liquid chromatography, and corresponding pharmacodynamics were determined by impedance aggregometry. Results Acetylsalicylic acid was rapidly absorbed with a mean Tmax of 27 ± 8 min. Tmax of salicylic acid was 69 ± 21 min. Mean Cmax was 1·8 ± 0·6 mg/L and 7·6 ± 1·4 for acetylsalicylic acid and salicylic acid, respectively. Arachidonic acid‐induced aggregation showed maximum platelet inhibition 30 min after drug ingestion. Conclusions The characterization of the plasma–time profile fills the gap between the lack of data on pharmacokinetics and the pharmacodynamics and the recommendation for using low‐dose chewable aspirin for acute coronary syndromes. We describe for the first time that a 162‐mg dose of chewable aspirin is rapidly absorbed and achieves plasma concentrations of the active metabolite salicylic acid required to maximally inhibit platelet aggregation. However, a 162‐mg dose is truly a minimum, and doubling this dose might be better for patients with myocardial infarction.